2020
DOI: 10.1093/braincomms/fcaa148
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-leucine slows disease progression in lysosomal storage disorders

Abstract: Acetyl-DL-leucine is a derivative of the branched chain amino acid leucine. In observational clinical studies acetyl-DL-leucine improved symptoms of ataxia, in particular in patients with the lysosomal storage disorder, Niemann-Pick disease type C1. Here, we investigated acetyl-DL-leucine and its enantiomers acetyl-L-leucine and acetyl-D-leucine in symptomatic Npc1-/- mice and observed improvement in ataxia with both individual enantiomers and acetyl-DL-leucine. When acetyl-DL-leucine and acetyl-L-leucine were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 54 publications
4
40
0
3
Order By: Relevance
“…This is in line with the previous observational studies that indicated the additive effect of NALL with Miglustat (Bremova et al, 2015;Cortina-Borja et al, 2018), and studies demonstrating synergistic effects of NALL and Miglustat (Kaya et al, 2020a). NALL's positive treatment effects directly correlate to its pharmacological action: Animal studies in an Npc1 -/mouse model show NALL significantly reduces ataxia when treatment is initiated either symptomatically (from 8-weeks of age) or pre-symptomatically (from 3-weeks of age) (Kaya et al, 2020a). These in vivo studies further show NALL can restore neuronal function and protect against/delay disease progression in multiple neurological brain circuits.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with the previous observational studies that indicated the additive effect of NALL with Miglustat (Bremova et al, 2015;Cortina-Borja et al, 2018), and studies demonstrating synergistic effects of NALL and Miglustat (Kaya et al, 2020a). NALL's positive treatment effects directly correlate to its pharmacological action: Animal studies in an Npc1 -/mouse model show NALL significantly reduces ataxia when treatment is initiated either symptomatically (from 8-weeks of age) or pre-symptomatically (from 3-weeks of age) (Kaya et al, 2020a). These in vivo studies further show NALL can restore neuronal function and protect against/delay disease progression in multiple neurological brain circuits.…”
Section: Discussionsupporting
confidence: 91%
“…In a case series, short-term treatment with N-acetyl-DL-leucine was found to improve ataxia, cognition, and quality of life in 12 patients with NPC (Bremova et al, 2015). Subsequent long-term case series and pre-clinical studies demonstrated the neuroprotective, disease modifying effect of treatment in NPC (Cortina-Borja et al, 2018; Kaya et al, 2020a). In all, the compound was well tolerated with no serious side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Kaya et al [ 48 ] reported that orally-administered N-acetyl-DL-leucine (ADLL) to NPC1 patients significantly retarded its rate of clinical disease progression, with improvements in or stabilization of a range of neurological domains. This agent also exerted beneficial effects on gait in patients afflicted with Tay-Sachs and Sandhoff diseases (GM2 gangliosidoses), and also in a mouse model of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, several mechanisms of action have been suggested including physicochemical partitioning into the phopspholipid bilayer to decrease its fluidity (Neuzil et al, 2002), direct action on glycine recptors and AMPA receptors (Neuzil et al, 2002), effects on branched chain aminotransferaes affecting glutamate neurotransmission (Kalla and Strupp, 2019), an increase in glucose metabolism (Kalla and Strupp, 2019). For the lysosomal storage disorder Niemann-Pick type C (NPC), N-acetyl-L-leucine mediates a shift in global cellular metabolism from glycolysis to oxidative phosphorylation for ATP production (Kaya et al, 2020), and in another lysosomal storage disorder Sandoff disease, it normalizes the aberant metabolism that results in oxidative stress (Kaya et al, 2020). All of the above mechanisms could contrribute to the observed effect of normalizing membrane potential and excitability leading to activation of the vestibulo-cerebellum and a deactivation of the posterolateral thalamus (Ferber-Viart et al, 2009; Kalla and Strupp, 2019; Vibert and Vidal, 2001).…”
Section: Introductionmentioning
confidence: 99%